2022
DOI: 10.1016/j.scitotenv.2021.151137
|View full text |Cite
|
Sign up to set email alerts
|

A review on measurements of SARS-CoV-2 genetic material in air in outdoor and indoor environments: Implication for airborne transmission

Abstract: Airborne transmission of SARS-CoV-2 has been object of debate in the scientific community since the beginning of COVID-19 pandemic. This mechanism of transmission could arise from virus-laden aerosol released by infected individuals and it is influenced by several factors. Among these, the concentration and size distribution of virus-laden particles play an important role. The knowledge regarding aerosol transmission increases as new evidence is collected in different studies, even if it is not yet available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 119 publications
3
60
0
Order By: Relevance
“…A study in Wuhan found that air samples collected using robot assisted air sampling from hospitals, were positive for SARS-CoV-2 and COVID-19 patients who had recovered and were ready for discharge, exhaled the virus in the air ( Zhou, Yao et al, 2021 ). A systematic review of 73 studies published on presence of SARS-CoV-2 RNA in air suggested that the concentration of SARS-CoV-2 RNA was higher in indoor air as compared to outdoor air and in indoor, it was higher in hospital and healthcare settings as compared to that in community indoor settings ( Dinoi, Feltracco et al, 2022 ). A pilot study on environmental sampling of SARS-CoV-2 in indoor residential settings involving two self-quarantined COVID-19 patients detected SARS-CoV-2 RNA in the air in the rooms ( Nannu Shankar, Witanachchi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Wuhan found that air samples collected using robot assisted air sampling from hospitals, were positive for SARS-CoV-2 and COVID-19 patients who had recovered and were ready for discharge, exhaled the virus in the air ( Zhou, Yao et al, 2021 ). A systematic review of 73 studies published on presence of SARS-CoV-2 RNA in air suggested that the concentration of SARS-CoV-2 RNA was higher in indoor air as compared to outdoor air and in indoor, it was higher in hospital and healthcare settings as compared to that in community indoor settings ( Dinoi, Feltracco et al, 2022 ). A pilot study on environmental sampling of SARS-CoV-2 in indoor residential settings involving two self-quarantined COVID-19 patients detected SARS-CoV-2 RNA in the air in the rooms ( Nannu Shankar, Witanachchi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, 58 datasets measuring airborne SARS-CoV-2 RNA traces in the air of hospitals and care facilities showed that 41 datasets were negative for presence of SARS-CoV-2 in a the all air samples or positive (at least one sample tested positive with PCR analysis) without quantification of concentrations, and 17 datasets (29.3% of the total studies) qualitatively examined virus concentrations in the air samples (Dinoi et al, 2021). Moreover, Ben-Shmuel et al ( 2020) investigated infectious titers of the virus in 97 positive air and surface samples in order to evaluate SARS-CoV-2 viability, and reported no infectious titers of the virus in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The most used filtering materials are polytetrafluoroethylene (PTFE), glass fiber, and quartz fiber. Thus, several researchers have adapted this method for finding SARS-CoV-2 RNA in the collected particulate matter and, in some cases, for assessing infectivity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Debates on the airborne transmission route of SARS-CoV-2 have been complicated because among the studies testing the presence of the virus in the air and/or on surfaces, the percentage of positive samples collected on surfaces was considerably higher than the air samples [4,7].…”
Section: Introductionmentioning
confidence: 99%